Performance related pay and firm productivity: New evidence from a quasi-natural experiment in Italy - Claudio Lucifora; Federica Origo (Institute for the Study of Labor (IZA), 2012)
This paper investigates the causal effect of a switch from fixed wages to collective performance-related pay on firm productivity, exploiting an exogenous variation in the institutional environment regulating collective bargaining. We find that the introduction of collective performance related pay significantly increases productivity by around 3-5 per cent, but such effect varies greatly by firm size, industry and union density. We show that the design of the PRP scheme - in terms of number and type of parameters used - is also relevant for firm productivity.
urn:nbn:de:101:1-2012080812255
Keywords: J31; J33; J52; L61; 330; performance related pay; productivity; unions; Leistungsentgelt; Tarifpolitik; Produktivität; Gewerkschaftsmitgliedschaft; Italien